PERANAN DALIHAN NA TOLU DALAM PROSES INTERAKSI PADA MASYARAKAT DESA PASAR MATANGGOR KECAMATAN BATANG ONANG - Ali Padang; Erwin Siregar (Jurnal TAROMBO, 2023)
A good understanding of the role Dalihan na tolu is a basic philosophical structure of social relationships among the Batak South Tapanuli Pasarmatanggor particular village, subdistrict Batang Onang which is a symbol of kinship Kahanggi, Children Boru and Mora. Similarly, if one of these relationships is not present in the session peradatan, impossible to be solved custom events discussed in the trial, while the kinship of this happened because of their marital relationship. This study was conducted aim to find out how the role of Dalihan na tolu in the process of interaction in rural communities Pasarmatanggor Values ​​Cultural contained in the mating system (Siulaon) the communities in Pasarmatanggor change as well, which was once the ceremony Manngupa in marriage newlyweds very valuable, but now these cultural values ​​is already experiencing changes due to daribangan the times are getting modren. The result of this research is the desire of the people now have a practical-practical course would not rambling and charged with the affairs of the customs that exist like the old days, so the ceremony Mangupa people assume just as symbolic and not so important to society because they are more bepikir logically and critically.